Similar incidence of graft glomerulonephritis in recipients with definitively diagnosed glomerulonephritis and those with unknown etiology: a retrospective observational study - Qianqian Wu; Xuefeng Ni; Jingsong Chen; Dongrui Cheng; Mingchao Zhang; Kenan Xie; Xue Li; Jiqiu Wen (Renal Failure)
Objective In China, most of the patients who underwent kidney transplants have unknown causes of end-stage renal disease (uESRD). However, little is known regarding the incidence of graft glomerulonephritis (GN) and graft survival in kidney transplant recipients (KTRs) with uESRD.Methods In this retrospective cohort study, 473 of the 565 KTRs who underwent kidney transplantation (KTx) from 2015 to 2020 were included. We mainly observed the occurrence of graft GN between uESRD group and definitively diagnosed GN group, and repeatedly compared after propensity score matching (PSM).Results The median follow-up was 50 months in 473 KTRs, and about 75% of KTRs of native kidney disease of unknown etiology. The total cumulative incidence of graft GN was 17%, and no difference was observed between the definitively diagnosed GN group and the uESRD group (p = 0.76). Further, PSM analysis also showed no difference in the incidence of graft GN between the 2 groups. Multivariable analysis disclosed males (p = 0.001), younger age (p = 0.03), and anti-endothelial cell anti-body (AECA) positive pre-KTx (p = 0.001) were independent risk factors for graft GN.Conclusions The incidence of graft GN was similar between uESRD and definitively diagnosed GN group. The allograft survival was also similar between two groups.